Communicating musical knowledge through gesture: Piano teachers' gestural behaviours across different levels of student proficiency. (September 2015) - Simones, Lilian Lima; Rodger, Matthew; Schroeder, Franziska
Teachers' communication of musical knowledge through physical gesture represents a valuable pedagogical field in need of investigation. This exploratory case study compares the gestural behaviour of three piano teachers while giving individual lessons to students who differed according to piano proficiency levels. The data was collected by video recordings of one-to-one piano lessons and gestures were categorized using two gesture classifications: the spontaneous co-verbal gesture classification (McNeill, 1992; 2005) and spontaneous co-musical gesture classification (Simones, Schroeder & Rodger, 2013). Poisson regression analysis and qualitative observation suggest a relationship between teachers' didactic intentions and the types of gesture they produced while teaching, as shown by differences in gestural category frequency between teaching students of higher and lower levels of proficiency. Such reported agreement between teachers' gestural approach in relation to student proficiency levels indicates a teachers' gestural scaffolding approach whereby teachers adapted gestural communicative channels to suit students' specific conceptual skill levels.